Analysis of quality in Brazilian e-commerce (B2C) - De Oliveira Costa Neto, Pedro Luiz; Fusco, José Paulo Alves [UNESP]; Dos Reis, João Gilberto Mendes (Springer-verlag Berlin, 2010)
The business world has changed the way how people think and act on products and services. In this context, the most recent amendment of the scenarios of retail operations has been the use of technology in sales and distribution. The internet has revolutionized the way people communicate, and moreover as they purchase their goods and services. Thus, the e-commerce, specifically the relation business to customer, or simply B2C, has acted so convincingly in this change of paradigm, namely the purchases in the physical location for the virtual site. Quotes online, ease of payment, price, speed of delivery, have become real order winners of applications for companies that compete in this segment. With the focus on quality of services on e-commerce, the research examines the dimension related to the quality of services, and looks for what of these factors are winners of applications. © 2010 IFIP International Federation for Information Processing.
Keywords: business to customer; dimensions of quality; order winners; quality of services; Supply chain; Business to customers; E-Commerce; Order winners; Physical locations; Products and services; Retail operations; Sales and distribution; Customer satisfaction; Electronic commerce; Management; Quality control; Supply chain management; Supply chains; Sales